The missing puzzle of indigenous crops in Tanzania’s agricultural trade - John, Innocensia; Gandidzanwa, Colleta (Frontiers in Sustainable Food Systems, 2025)
Existing trade policies in Tanzania can potentially boost or undermine Indigenous crop representation in both domestic and international trade. The trade potential is heavily reliant on the effectiveness of existing trade policies. This paper examines the existing trade policies related to indigenous crops in Tanzania, the challenges faced, and potential strategies to enhance their market integration and trade potential. It uses a mixed methods approach consisting of qualitative and quantitative trend analysis. A policy review process is used to assess the existing policies and their effectiveness in enhancing the trade potential of indigenous crops. The results suggest that existing policies do not sufficiently encompass indigenous crops and that the trade potential of indigenous crops still needs to be realized, with only three crops out of 28 (cassava, sorghum, cowpea) crops available in Tanzania having trade recognition in the international markets. Most indigenous crops remain in domestic markets, with very few reaching urban markets, while most remain in rural markets. Moreover, most of the policies and regulations available in Tanzania have yet to recognize these crops within the policies. This paper contributes to the development of policies that support the inclusion of indigenous crops in trade. It emphasizes the need for a comprehensive review of existing government policies to unlock the trade potential of indigenous crops, recognizing their critical role in Tanzania’s agricultural heritage and food security.